Oncolytic viruses in cancer therapy - Vähä-Koskela, Markus J.V. (Cancer Lett, 2007)
Oncolytic virotherapy is a promising form of gene therapy for cancer, employing nature’s own agents to find and destroy malignant cells. The purpose of this review is to provide an introduction to this very topical field of research and to point out some of the current observations, insights and ideas circulating in the literature. We have strived to acknowledge as many different oncolytic viruses as possible to give a broader picture of targeting cancer using viruses. Some of the newest additions to the panel of oncolytic viruses include the avian adenovirus, foamy virus, myxoma virus, yaba-like disease virus, echovirus type 1, bovine herpesvirus 4, Saimiri virus, feline panleukopenia virus, Sendai virus and the non-human coronaviruses. Although promising, virotherapy still faces many obstacles that need to be addressed, including the emergence of virus-resistant tumor cells.